Effect of 'Fluorophenylammonium' and 'Fluorophenethylammonium' as Spacer on the Photo(electro)chemical and Photocatalytic Behaviour of Mixed Halide Based Layered Perovskites. Issue 45 (1st December 2022) - Mondal, Arindam; Gupta, Satyajit
Abstract: Two‐dimensional lead (Pb 2+ ) based halide perovskites (2D‐PbHaPs) with a structural formula of R2 PbX4 (where R=organic amine and X=Cl, Br or I) represents a 'layered' structure, having better stability compared to three‐dimensional lead halide perovskites (3D‐PbHaPs) such as APbX3 (where A=methylammonium and X=Cl, Br or I). The choice of 'R' site, which acts as a 'spacer' in the PbX6 4− octahedral framework, is critical in determining the optical and electrical properties of the 2D‐PbHaP based semiconductors. In this study, two different spacers [4‐fluorophenethylammonium‐FC6 H4 −CH2 −CH2 −NH3 + ; abbreviated as FPEA and 4‐fluorophenylammonium‐FC6 H4 −NH3 + ; abbreviated as FPA] are selected as 'R' site of the 2D framework of 'mixed halide' based 2D‐PbHaP systems [(FPEA)2 PbI2 Br2 and (FPA)2 PbI2 Br2 )], to examine the impact of the 'spacer' on the optical properties, photo(electro)chemical, and photocatalytic behavior in the form of thin‐films. The thin films were having an approximate thickness of 325±25 nm. The bandgap (EBG ) and photo‐luminescence peak of (FPA)2 PbI2 Br2 was observed to be red‐shifted compared to (FPEA)2 PbI2 Br2 . Chronoamperometry and linear sweep voltammetry (LSV) analysis indicated a ∼100 % improvement in the photo‐current density for (FPA)2 PbI2 Br2 compared to (FPEA)2 PbI2 Br2 . Furthermore, the (FPA)2 PbI2 Br2 based system showed better photocatalytic activity towards degradation of methylene blue and S−S coupling reactions, compared to (FPEA)2 PbI2 Br2 . Abstract : The study reveals that smaller spacer‐ FPA (Fluorophenylammonium) in R site of mixed halide‐based 2D‐PbHaPs (R2 PbI2 Br2 ) a) red‐shifts the band gap, b) increases photo‐current density by two times, d) decreases charge transfer resistance, and e) enhances photocatalytic activity, compared to longer spacer‐FPEA (Fluorophenethylammonium).